Overcoming the resistance of hepatocellular carcinoma to PD-1/PD-L1 inhibitor and the resultant immunosuppression by CD38 siRNA-loaded extracellular vesicles - Jun Deng; Hui Ke (OncoImmunology, 2023)
Extracellular vesicles (EVs) are promising tools for drug delivery across different biological barriers. Here, we evaluated the potential of EVs-mediated delivery of CD38 siRNA on the immunosuppression of hepatocellular carcinoma (HCC). EVs were isolated from bone marrow mesenchymal stem cell culture medium and loaded with CD38 siRNA to prepare EVs/siCD38. Loss-of-function assays were conducted to investigate the biological functions of EVs/siCD38 in HCC cells. Xenograft mouse models were performed for further validation. High CD38 expression was found in HCC. EVs/siCD38 inhibited CD38 enzyme activity, decreased adenosine production, and promoted macrophage repolarization to M1 type, thus inhibiting HCC cell growth and metastasis in vitro as well as tumor growth in mice. Mechanistically, CD38 was upregulated in mice resistant to PD-1/PD-L1 inhibitor and EVs/siCD38 reversed the resistance of tumor to PD-1/PD-L1 inhibitor in vivo. Our results provide functional evidence for the use of EV-mediated delivery of CD38 siRNA to prevent immunosuppression feature of HCC.